Enantioselective Direct α-Amination of Aldehydes via a Photoredox Mechanism: A Strategy for Asymmetric Amine Fragment Coupling - Cecere, Giuseppe (2013)
The direct, asymmetric α-amination of aldehydes has been accomplished via a combination of photoredox and organocatalysis. Photon-generated, nitrogen-centered radicals undergo enantioselective α-addition to catalytically formed chiral enamines to directly produce stable α-amino aldehyde adducts bearing synthetically useful amine substitution patterns. Incorporation of a photolabile group on the amine precursor obviates the need to employ a photoredox catalyst in this transformation. Importantly, this photoinduced transformation allows direct and enantioselective access to α-amino aldehyde products that do not require post-reaction manipulation.